Ricordi? [videorecording (DVD)] - Marinelli, Luca; Caridi, Linda; Anzaldo, Giovanni, 1987- (Distrib Films, 2020)
A love story, seen through the memories of one young couple: recollections altered by moods, different perspectives, and time itself. A journey through the years of two individuals, united, divided, happy, unhappy, deeply in love or in love with others, told in a single stream of emotions and shades of feeling. Over the course of the film, he learns that love can last, while she learns to live with nostalgia.